In vitro investigation on synergistic anticancer effects between vitamin E isomers, pure compounds and crude alkaloid plant extracts on human cancerous cells - Abubakar, Ibrahim Babangida (2017)
Anticancer chemotherapeutic treatment using single dose has been limited due to drug resistance and potential metabolic degradation. For instance, high-dose tocotrienols undergo metabolic degradation that limits the availability of therapeutic dose thereby limiting the potency in vivo. Combined treatment of tocotrienols at low dosage has been suggested as alternative to circumventing this limitation. This study was designed to investigate the cytotoxic effects and subsequently the apoptotic mechanisms of individual doses and combined treatments at lower dosages of tocotrienols (delta and gamma), jerantinines (A and B) and extracts (ethanol and alkaloid crude) from leaves and bark of Ficus hispida, Ficus fistulosa and Ficus schwarzii on lung (A549), brain (U87MG) and colon (HT-29) cancer cell lines. Neutral red uptake assay was conducted to evaluate the antiproliferative effect of individual and combined treatments. Staining techniques (histochemical and fluorescence), COMET assay flow cytometric analysis and immunofluorescence were conducted to evaluate cell morphology, DNA damage, cell cycle arrest pattern and antimicrotubule effects. Finally cell and molecular based assays were conducted to investigate the pathways for induction of apoptosis.